Personality traits and alcohol consumption in university students - Lopez-Cisneros, Manuel (Universidad de Sonora, 2021)
Introduction: Personality traits are persistent patterns of behavior in the way of thinking, perceiving and relating, so they serve as determining factors that can make the individual vulnerable to acquire behaviors that are healthy or harmful to health, such as the use of licit drugs and illicit. Objective: To determine the relationship between personality traits and alcohol consumption in university students from Ciudad del Carmen Campeche, Mexico. Methodology: Quantitative, non-experimental, descriptive correlational, cross sectional study, carried out on a sample of 238 university students in the health area. Results: The lapsed prevalence of alcohol consumption was presented in a higher proportion (85.3%), compared to the current prevalence (39.9%) and instantaneous (20.6%). Regarding the type of alcohol consumption, there is a dependent consumption (19.9%) in university students, despite the prevalence of risky consumption (60.2%). According to AUDIT, a positive relationship was found with the extraversion personality trait (rs = .165, p = .02). Conclusions: The profile of alcohol consumption in young people was identified, as well as a relationship of the extraversion personality trait with alcohol consumption, which highlights the need for the design and implementation of efficient and timely nursing interventions that contribute significantly to the reduction and eradication of harmful habits for health and the promotion of healthy lifestyles.